A Panel Data Analysis of Relationship between Migration and Inequality. (January 2017) - John, Raju
In this article, the relationship between migration and inequality in India is analyzed on the basis of an understanding of the role of migration in creating inequalities in the economy and society of the state of Kerala. The Centre for Development Studies (CDS), Thiruvanathapuram, Kerala, conducts periodic Kerala Migration Surveys (KMSs) to monitor the current status of emigration from and return emigration to the state of Kerala. This data set is used to discover the dynamics of migration–inequality relationship in the state. The results of the study suggest that migration causes inequalities in mobility between migrant and non-migrant households and between different types of migrant households.